Brain Health Initiatives for Pakistan - Mohammad Wasay; Naila Shahbaz; Safa Younis; Abdul Malik (Journal of the Pakistan Medical Association, 2024)
Brain health can be defined as the state of brain functioning across sensory, cognitive, social-emotional, behavioural, and motor domains—the combination of which allows a human being to realize their full potential over the course of their life, regardless of the presence or absence of neurological disorders.1 When brain health is prioritised and optimised, mental and physical health are also improved, which correlates with positive economic and social impacts. All of these contribute to a more prosperous and healthy society. However, developing countries such as Pakistan are at a disadvantage due to antecedent conditions like environmental factors and deprioritisation of brain health in both policy and national finances. This editorial delineates brain health initiatives for Pakistan, drawing on WHO frameworks and other countries’ proactive endeavours. Continue...